ProSeal Laryngeal Mask Airway Attenuates Systemic and Cerebral Hemodynamic Response During Awakening of Neurosurgical Patients: A Randomized Clinical Trial. Issue 3 (July 2015) - Perelló-Cerdà, Laura; Fàbregas, Neus; López, Ana M.; Rios, José; Tercero, Javier; Carrero, Enrique; Hurtado, Paola; Hervías, Adriana; Gracia, Isabel; Caral, Luis; de Riva, Nicolás; Valero, Ricard
Abstract : Background: Extubation and emergence from anesthesia may lead to systemic and cerebral hemodynamic changes that endanger neurosurgical patients. We aimed to compare systemic and cerebral hemodynamic variables and cough incidence in neurosurgery patients emerging from general anesthesia with the standard procedure (endotracheal tube [ETT] extubation) or after replacement of the ETT with a laryngeal mask airway (LMA). Materials and Methods: Forty-two patients undergoing supratentorial craniotomy under general anesthesia were included in a randomized open-label parallel trial. Patients were randomized (sealed envelopes labeled with software-generated randomized numbers) to awaken with the ETT in place or after its replacement with a ProSeal LMA. We recorded mean arterial pressure as the primary endpoint and heart rate, middle cerebral artery flow velocity, regional cerebral oxygen saturation, norepinephrine plasma concentrations, and coughing. Results: No differences were found between groups at baseline. All hemodynamic variables increased significantly from baseline in both groups during emergence. The ETT group had significantly higher mean arterial pressure (11.9 mm Hg; 95% confidence interval [CI], 2.1-21.8 mm Hg) ( P =0.017), heart rate (7.2 beats/min; 95% CI, 0.7-13.7 beats/min) ( P =0.03), and rate-pressure product (1045.4; 95% CI, 440.8-1650) ( P =0.001). Antihypertensive medication was administered to more ETT-group patients than LMA-group patients (9 [42.9%] vs. 3 [14.3%] patients, respectively; P =0.04). The percent increase in regional cerebral oxygen saturation was greater in the ETT group by 26.1% (95% CI, 9.1%-43.2%) ( P =0.002), but no between-group differences were found in MCA flow velocity. Norepinephrine plasma concentrations rose in both groups between baseline and the end of emergence: LMA: from 87.5±7.1 to 125.6±17.3 pg/mL; and ETT: from 118.1±14.1 to 158.1±24.7 pg/mL ( P =0.007). The differences between groups were not significant. The incidence of cough was higher in the ETT group (87.5%) than in the LMA group (9.5%) ( P <0.001). Conclusions: Replacing the ETT with the LMA before neurosurgical patients emerge from anesthesia results in a more favorable hemodynamic profile, less cerebral hyperemia, and a lower incidence of cough.